EVALUASI IMPLEMENTASI TAMBAHAN PENGHASILAN PEGAWAI NEGERI SIPIL - Ihsan, Nur (Jurnal Ilmu Administrasi Negara, 2017)
Abstract: Evaluation of the Implementation of Civil Servants Income Supplement. Thisstudy aims to evaluate the implementation of policies and look at the factors that influence policyimplementation Income Supplement Civil Servants. The method used is descriptive explanatorywith a qualitative approach. The technique of collecting data using interviews, direct observation,documentation. Determination of informants pusposive engineering research with samplingand snowball sampling. The process of data analysis with interactive analysis. Implementationof additional policies have been implemented employee income well as payments are made ona regular basis each month, in accordance with the level of discipline and work performance ofemployees.